História Indígena nas Propostas Curriculares Oficiais (2008-2016) - Costa, Fernanda Pereira Da [UNIFESP] (2020)
This research aims to analyze official curricular proposals of History teaching, from different Brazilian states, in its different formats and developments, preferably after the institution of Law 11.645/2008. More precisely, we intend to investigate how the history and culture of indigenous peoples have been approached in these documents. We will first make an inventory of official curricular proposals and the different narratives that these materials convey about the Amerindian peoples. After that, we will confront these representations with those presented in the academic production on indigenous history and teaching history, especially of the last three decades. The field of Education, particularly the studies on curriculum theory and critical interculturality, will provide the theoretical support of this research. By thinking about the relationship between the knowledge produced in the academy, which has strong influences of the social and indigenous movements, and the curricula we hope to demonstrate how the first affects the latter. Therefore, we expect to understand how, after the promulgation of Law 11.645/08, the didactic proposals elaborated by the states collaborate to train students to recognize the indigenous populations as historical subjects that should be viewed under the prism of equality in difference, in order to ensure an education that creates new paradigms of intercultural relationships.